Circulating immune markers and risks of non‐Hodgkin lymphoma subtypes: A pooled analysis. Issue 5 (5th October 2022) - Rhee, Jongeun; Birmann, Brenda M.; De Roos, Anneclaire J.; Epstein, Mara M.; Martinez‐Maza, Otoniel; Breen, Elizabeth C.; Magpantay, Larry I.; Levin, Lynn I.; Visvanathan, Kala; Hosgood, H. Dean; Rohan, Thomas E.; Smoller, Sylvia W.; et al.
Abstract: Although prediagnostic circulating concentrations of the immune activation markers soluble CD27 (sCD27), sCD30 and chemokine ligand‐13 (CXCL13) have been associated with non‐Hodgkin lymphoma (NHL) risk, studies have been limited by sample size in associations with NHL subtypes. We pooled data from eight nested case‐control studies to investigate subtype‐specific relationships for these analytes. Using polytomous regression, we calculated odds ratios (ORs) with 95% confidence intervals (CIs) relating study‐specific analyte tertiles to selected subtypes vs controls (n = 3310): chronic lymphocytic leukemia/small lymphocytic lymphoma (CLL/SLL; n = 623), diffuse large B cell lymphoma (DLBCL; n = 621), follicular lymphoma (FL; n = 398), marginal zone lymphoma (MZL; n = 138), mantle cell lymphoma (MCL; n = 82) and T cell lymphoma (TCL; n = 92). We observed associations with DLBCL for elevated sCD27 [OR for third vs first tertile (ORT3 ) = 2.2, 95% CI = 1.6‐3.1], sCD30 (ORT3 = 2.0, 95% CI = 1.6‐2.5) and CXCL13 (ORT3 = 2.3, 95% CI = 1.8‐3.0). We also observed associations with sCD27 for CLL/SLL (ORT3 = 3.3, 95% CI = 2.4‐4.6), MZL (ORT3 = 7.7, 95% CI = 3.0‐20.1) and TCL (ORT3 = 3.4, 95% CI = 1.5‐7.7), and between sCD30 and FL (ORT3 = 2.7, 95% CI = 2.0‐3.5). In analyses stratified by time from phlebotomy to case diagnosis, the sCD27‐TCL and all three DLBCL associations were equivalent across both follow‐up periods (<7.5, ≥7.5 years). For other analyte‐subtype comparisons, associations were stronger for the follow‐up period closer to phlebotomy, particularly for indolent subtypes. In conclusion, we found robust evidence of an association between these immune markers and DLBCL, consistent with hypotheses that mechanisms related to immune activation are important in its pathogenesis. Our other findings, particularly for the rarer subtypes MZL and TCL, require further investigation. Abstract : What's new? Although prediagnostic circulating concentrations of the immune activation markers sCD27, sCD30 and CXCL13 have been associated with non‐Hodgkin lymphoma risk, studies have been limited by sample size in associations with non‐Hodgkin lymphoma subtypes. This pooled analysis of the three prediagnostic serum immune marker concentrations and non‐Hodgkin lymphoma subtypes, the first of its kind, provides robust evidence implicating subclinical immune activation effects in the pathogenesis of diffuse large B cell lymphoma. The results also offer novel insights into the etiologies of rare lymphomas such as marginal zone and T cell lymphomas.